ASSESSMENT OF VITAMIN D THERAPY EFFECT ON INFLAMMATORY MARKERS IN PEDIATRIC PATIENTS WITH TYPE I DIABETIC - Kadhim, Kadhim Ali; Nafea, Lubab Tarek; Gasim, Gaith Ali; Hameed, Esraa Abdul-al; Fawzi, Hayder A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to estimate the effect of Vitamin D3 supplementation on endogenous Vitamin D3 level and inflammatory biomarkers in newly diagnosed pediatric patients. Methods: The patients were given oral Vitamin D3, and they divided into three groups: The first group (25 healthy pediatrics), the second group (25 newly diagnosed pediatric patients) treated with daily insulin regimen only, and the third group (25 newly diagnosed pediatric patients) treated with Vitamin D3 (2000 IU/day) with daily insulin regimen; all patients were treated for 90 days; and blood samples were taken at baseline and after 45 days and 90 days of starting Vitamin D3 to assess its potential effect on the levels of Vitamin D, serum calcium, serum alkaline phosphatase levels, and other inflammatory markers. Results: The results of the current study showed that serum IL-1Î² significantly declined in patients receiving Vitamin D3, while serum Vitamin D3, serum calcium, and interleukins-4 were significantly increased in patients receiving Vitamin D3. Conclusion: Vitamin D3 in a daily dose of 2000 IU/day for 90 days results in favorable immune response and increase of serum Vitamin D3 for pediatric new diagnosed Type 1 diabetes mellitus patients.